1995
DOI: 10.1128/aem.61.1.145-151.1995
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradation of naphthalene in aqueous nonionic surfactant systems

Abstract: The principal objective of this study was to quantify the bioavailability of micelle-solubilized naphthalene to naphthalene-degrading microorganisms comprising a mixed population isolated from contaminated waste and soils. Two nonionic surfactants were used, an alkylethoxylate, Brij 30 (C 12 E 4), and an alkylphenol ethoxylate, Triton X-100 (C 8 PE 9.5). Batch experiments were used to evaluate the effects of aqueous, micellized nonionic surfactants on the microbial mineralization of naphthalene and salicylic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
74
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 179 publications
(76 citation statements)
references
References 27 publications
2
74
0
Order By: Relevance
“…The more hydrophobic surfactants exhibited better solubilizing properties. Contradictory results have been obtained from tests on biodegradability of PAH solubilized by synthetic surfactants (Liu et al 1995). Tiehm (1994) showed that bacteria were less tolerant to the more hydrophobic surfactants.…”
Section: Surfactants and Bioremediationmentioning
confidence: 99%
“…The more hydrophobic surfactants exhibited better solubilizing properties. Contradictory results have been obtained from tests on biodegradability of PAH solubilized by synthetic surfactants (Liu et al 1995). Tiehm (1994) showed that bacteria were less tolerant to the more hydrophobic surfactants.…”
Section: Surfactants and Bioremediationmentioning
confidence: 99%
“…There have been a number of studies on the effectiveness of surfactants on biodegradation of PAHs, but results are inconclusive. Some reports have demonstrated that nonionic surfactants stimulate the biodegradation of PAH in liquid or soil systems (Guerin & Jones, 1988;Tiehm, 1994;Liu et al, 1995;Sartoros et al, 2005). However, in other cases the presence of surfactants resulted in no or decreased PAH degradation (Tiehm, 1994;Lei et al, 2005;Li & Bai, 2005;Sartoros et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…A number of investigators have demonstrated that surfactants can enhance bioavailability of PAHs by increasing rates of their mass transfer (e.g., dissolution or desorption) to the aqueous phase in which microbial uptake occurs [2][3][4][5], or micelle-associated PAHs are directly available to PAH-degrading microbes via direct contact between micelles and microbes [6,7]. The extent of stimulation varies with the type and concentration of surfactants and the type of microorganisms involved [8][9][10][11][12][13]. Conversely, others have reported surfactant additions to inhibit, or at least not enhance, PAH biodegradation [14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%